The Tanggapan Pembaca dalam Komunitas Cybersastra Goodreads terhadap Novel Hello Cello Karya Nadia Ristivani - Agustini, Ni Putu Rani; sudewa, I Ketut; Banda, Maria Matildis (Suara Bahasa, 2024)
The development of literature in the age of information technology is very rapid. Literature that appears on the internet is called cyber literature or cyberliterature. The novel Hello Cello by Nadia Ristivani is one of the novels that started from cyberliterature. In the goodreads cybersastra community, Nadia Ristivani's novel Hello Cello received a rating of 4.42/5 with 200 reviews. The high rating obtained by the Hello Cello novel is the reason for researchers to research how readers respond to the novel. The researcher used fifteen data taken from the goodreads cyberliterature community. Of the thirteen data, the researcher obtained six responses to the main characters in the novel. Five readers' responses to the novel's plot. Four readers' responses to Nadia Ristivani's Hello Cello as a novel adaptation of Twitter's alternate universe. Based on the data obtained, the researcher concluded that the novel Hello Cello by Nadia Ristivani has a strong and dominating character so that it can bring the feelings of the readers in it, then this novel has a mixed plot, where the plot is slow at the beginning but fast at the end and has a good narrative for an alternate universe adaptation novel. Nadia managed to write a good narrative and make the reader satisfied when reading it.